Cilostazol, Not Aspirin, Prevents Stenosis of Bioresorbable Vascular Grafts in a Venous Model. Issue 9 (September 2015) - Tara, Shuhei; Kurobe, Hirotsugu; de Dios Ruiz Rosado, Juan; Best, Cameron A.; Shoji, Toshihiro; Mahler, Nathan; Yi, Tai; Lee, Yong-Ung; Sugiura, Tadahisa; Hibino, Narutoshi; Partida-Sanchez, Santiago; Breuer, Christopher K.; et al.
<x xml:space="preserve">Abstract</x> Objective— Despite successful translation of bioresorbable vascular grafts for the repair of congenital heart disease, stenosis remains the primary cause of graft failure. In this study, we investigated the efficacy of long-term treatment with the antiplatelet drugs, aspirin and cilostazol, in preventing stenosis and evaluated the effect of these drugs on the acute phase of inflammation and tissue remodeling. Approach and Results— C57BL/6 mice were fed a drug-mixed diet of aspirin, cilostazol, or normal chow during the course of follow-up. Bioresorbable vascular grafts, composed of poly(glycolic acid) mesh sealed with poly(l-lactide-co-ε-caprolactone), were implanted as inferior vena cava interposition conduits and followed up for 2 weeks (n=10 per group) or 24 weeks (n=15 per group). Both aspirin and cilostazol suppressed platelet activation and attachment onto the grafts. On explant at 24 weeks, well-organized neotissue had developed, and cilostazol treatment resulted in 100% graft patency followed by the aspirin (67%) and no-treatment (60%) groups (P<0.05). Wall thickness and smooth muscle cell proliferation in the neotissue of the cilostazol group were decreased when compared with that of the no-treatment group at 24 weeks. In addition, cilostazol was shown to have an anti-inflammatory effect on neotissue at 2 weeks by regulating the recruitment and activation of monocytes. Conclusions— Cilostazol prevents stenosis of bioresorbable vascular graft in a mouse inferior vena cava implantation model up to 24 weeks and is accompanied by reduction of smooth muscle cell proliferation and acute inflammation.